(3GdEJMGO GdCQhHj hGdYedI GdCQhHjI GdehMOI(B"(3GdjhQh(B" (3hGdShb GdYQHjI GdeTJQcI (B:s (3OQGSGJ fXQjI hJWHjbjI dbVGjG EbJUGOjI eYGUQI (B/s - (3GdSjSj, UdGM GdOjf MSfs ((3GdbGgQI(B: s (3YGde GdcJGH(B, s, 2002)
(3GdEJMGO GdCQhHj(B- (3ChQhHG GdehMOI(B- (3GdCKGQ GdEbJUGOjI ddEJMGO GdfbOj GdCQhHj(B- (3GdShb GdYQHjI GdeTJQcI GdhGbY hGdWehM(B- (3GdJcGed GdEbJUGOj GdYQHj(B- (3efWbI GdJLGQI GdMQI GdYQHjI GdcHQi(B- (3GdShb GdYQHjI GdeTJQcI(B.s
Keywords: (3GdEJMGO GdCQhHjs; (3GdShb GdYQHjIs; (3GdYedI GdCQhHjIs